1968
DOI: 10.1139/p68-082
|View full text |Cite
|
Sign up to set email alerts
|

Ion implantation of silicon and germanium at room temperature. Analysis by means of 1.0-MeV helium ion scattering

Abstract: The orientation dependence of the backscattered yield of 1.0-MeV helium ions has been used to investigate the lattice characteristics of silicon and germanium implanted at room temperature with 40-keV heavy ions (Ga, As, Sb, In, P). The method gives directly the number of substrate atoms displaced from their lattice sites by more than the Thomas–Fermi screening distance (≈ 0.2 Å) and also the location of the implanted atoms.Each heavy ion is found to displace several thousand lattice atoms in a localized regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

1970
1970
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(51 citation statements)
references
References 0 publications
4
46
0
1
Order By: Relevance
“…Radiation damage is known to cause donor 2 and acceptor 3 states in the bandgap of many semiconductors, through the formation of vacancies and interstitials, which, on annealing, interact with hydrogen, oxygen, or dopant atoms already present in the lattice structure. The published literature on the annealing behavior of the damaged and amorphous Ge after ion implantation is mainly limited to the heavy ions ͑e.g., Ga, As, Sb, In, P, 4 Si, and Ge 5,6 ͒ at medium 6,7 ͑10 14 atoms/cm 2 ͒ to low ͑10 12 atoms/cm 2 ͒ fluences. In all the cases the maximum annealing required for full recrystallization was 500°C for 30 min.…”
mentioning
confidence: 99%
“…Radiation damage is known to cause donor 2 and acceptor 3 states in the bandgap of many semiconductors, through the formation of vacancies and interstitials, which, on annealing, interact with hydrogen, oxygen, or dopant atoms already present in the lattice structure. The published literature on the annealing behavior of the damaged and amorphous Ge after ion implantation is mainly limited to the heavy ions ͑e.g., Ga, As, Sb, In, P, 4 Si, and Ge 5,6 ͒ at medium 6,7 ͑10 14 atoms/cm 2 ͒ to low ͑10 12 atoms/cm 2 ͒ fluences. In all the cases the maximum annealing required for full recrystallization was 500°C for 30 min.…”
mentioning
confidence: 99%
“…This is in good agreement with the XTEM observations. Previous studies have shown, that recrystallization of an amorphous silicon layer by solid phase epitaxy is achievable at the present anneal temperature [149,150]. Due to the high concentration of hydrogen in the implantation zone and its interaction with lattice defects, which prohibits recrystallization of the silicon, only the shallow part of the amorphous layer recrystallized.…”
Section: As-implantedmentioning
confidence: 85%
“…The thickness of this layer is of the nrder of 2RP, where RP is the average projected range of the incident ions. 4 There are several variables that affect the ion dose required to form an amorphous layer. The ion species is critical 5 since heavy ions cause amorphitization more readily.…”
Section: Amorphous Layer Formationmentioning
confidence: 99%